2021
DOI: 10.1021/acssuschemeng.0c08466
|View full text |Cite
|
Sign up to set email alerts
|

A High-Performance Zinc-Organic Framework with Accessible Open Metal Sites Catalyzes CO2 and Styrene Oxide into Styrene Carbonate under Mild Conditions

Abstract: A new tetratopic bridging ligand 1,1′-(propane-1,3diyl)bis(1H-pyrazole-3,5-dicarboxylic acid) (PDC) with functional pyrazole groups was designed and used for reacting with environmentally friendly zinc centers in mixed solvents; the resulting framework [Zn 3.5 (PDC) 2 (H 2 O) 10 ] (abbreviated as MOF Zn-2PDC) contained numerous organic−inorganic crablike blocks and had high density of zinc sites and coordinated water molecules. Abundant open metal sites (OMSs) were generated after the removal of coordinated wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…All of the molecular sizes of epoxide derivatives can be found in Table S4. In addition, the turnover number (TON) value of styrene oxide in the presence of NUC-38Yb is 768, which is much better than most reported MOF catalysts, such as TCM-16­(Zr) (185), Zn-2PDC (181), and [Ni­(muco)­(bpa)­(H 2 O) 2 ] (163) (Table S5); this can be ascribed to the profitable contribution of [Yb 4 (μ 3 –OH) 2 (μ 2 –HCO 2 )­(H 2 O) 2 ] clusters and pyridine groups on the surface of the channels. Moreover, comparative runs for the cycloaddition reactions using NUC-38Ho as the catalyst were carried out under optimal reaction conditions.…”
Section: Resultsmentioning
confidence: 90%
“…All of the molecular sizes of epoxide derivatives can be found in Table S4. In addition, the turnover number (TON) value of styrene oxide in the presence of NUC-38Yb is 768, which is much better than most reported MOF catalysts, such as TCM-16­(Zr) (185), Zn-2PDC (181), and [Ni­(muco)­(bpa)­(H 2 O) 2 ] (163) (Table S5); this can be ascribed to the profitable contribution of [Yb 4 (μ 3 –OH) 2 (μ 2 –HCO 2 )­(H 2 O) 2 ] clusters and pyridine groups on the surface of the channels. Moreover, comparative runs for the cycloaddition reactions using NUC-38Ho as the catalyst were carried out under optimal reaction conditions.…”
Section: Resultsmentioning
confidence: 90%
“…The coexistence of the Lewis acidic Eu III with vacant coordination sites and the Brønsted acidic −COOH and −OH as well as the Lewis basic −NN– bond, the phenyl rings, and the lone-paired electron containing O atoms in the vicinity of Eu III (Figure ) should, in principle, promote the catalytic activities of Ib and IIb. …”
Section: Resultsmentioning
confidence: 99%
“…The copresence of Lewis acidic and basic motifs within the frameworks was also reported to enhance the catalysis since the Lewis basic motifs can help in transfixing CO 2 in close vicinity of the Lewis acid. Some previous CPs/MOFs devised based on this strategy were through the use of, for instance, the lone-paired electron containing N atom of 1,1′-(propane-1,3-diyl)­bis­(1 H -pyrazole-3,5-dicarboxylic acid) (PDC) in [Zn 3.5 (PDC) 2 (H 2 O) 10 ] and (5-5′-(1 H -1,2,4-triazole-3,5-diyl) diisophthalic acid in copper-based MOFs and the uncoordinated carboxylate O atoms in {[(CH 3 ) 2 NH 2 ]­[Zn II Tb III (TDP)­(H 2 O)]·3DMF·3H 2 O} n . Apart from the Lewis acidic and basic motifs, the catalytic activities of CPs/MOFs can also be improved in the presence of Brønsted acids, which may interact with both CO 2 and epoxide, e.g., −OH in [Zn 5 (OH) 2 (DBTA) 2 (H 2 O) 4 ] (H 4 DBTA = 2,2′-dihydroxy-1,1′-binaphthyl-3,3′,6,6′-tetrakis-(4-benzoic acid)) and −NH 2 as well as −COOH in [Zn 3 (L) 3 (H 2 L)·2DMF·H 2 O] (L = 2-aminoterephthalic acid) …”
Section: Introductionmentioning
confidence: 99%
“…Then the In1 ion is further bridged to the Zn1 ion by three other 4-position carboxyl groups offered by three distinct TDP 6− ligands (Figure 1e) to form one paddlewheel dinuclear As for the topological structure of NUC-42, the trigeminal TDP 6− ligand and binuclear {InZn} cluster can both be defined as five-connected nodes. Therefore, the whole structure of NUC-42 can be ascribed to one binodal fiveconnected fng-type framework with the Schlafi symbol of {4 6 .6 4 } shown in Figure 1d.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The design and synthesis of porous metal–organic frameworks (MOFs) have aroused great attention because of their promising application in a series of regions, such as polytypic catalysis, fluorescence sensing, drug delivery, gas separation/storage, magnetism, optoelectronics, and so on. Since the first report of MOF-catalyzed cycloaddition by Han et al, there have been a lot of studies on CO 2 cycloaddition catalyzed by various MOFs, which are differentiated by their constituents and connectivities. In terms of documented references, indium-based organic frameworks (In-OFs) have become a basically reliable heterogeneous catalyst because of the unique traits of In 3+ ion including accessible high-level p orbitals, diverse coordination numbers, and distinctive electronic configurations, which render them the ability to serve as facile Lewis acid sites to activate the involved reactants of CO 2 and epoxides during the chemical conversion of epoxides to cyclocarbonates. Moreover, in the past few years, zinc-based MOFs (Zn-MOFs) with well-ordered structures or networks are also well developed for a confirmed high catalytic performance on the chemical fixation of CO 2 under mild solvent-free conditions because of their moderate Lewis acidity and affinity to CO 2 and epoxide molecules from 3d 10 zinc cations. In 2013, Williams et al first reported that heterodinuclear MOF catalysts exhibited evidently higher activity upon the cycloaddition or copolymerization of CO 2 and epoxide than the homodinuclear ones, which might be due to the fact that the combination of chemically dissimilar metals displayed discrepant bimetallic surfaces and a high concentration of regularly distributed Lewis acid sites. So far, although the coexisting secondary building units (SBUs) of {InM 2 }, {In 2 M 2 }, {In 3 Ln}, and {In 3 Ln 2 } are reported, , the oriented strategy of integrating In 3+ 5p and Zn 2+ 3d metal elements into one SBU as inorganic nodes in MOFs has not yet been explored, maybe because the high and multifarious coordination numbers of In 3+ and Zn 2+ ions facially lead to their incompatibility.…”
Section: Introductionmentioning
confidence: 99%